2020
DOI: 10.1055/a-1128-6424
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Health-Related Quality of Life in Different Types of Chronic Ankle Instability

Abstract: Introduction People with chronic ankle instability (CAI) have decreased health-related quality of life (HRQOL), but the differences in HRQOL status between subgroups of CAI have not been determined. This observational, cross-sectional study aimed to evaluate and compare physical, social and psychological aspects of HRQOL in subgroups of patients with CAI. Methods Ninety patients with CAI and 30 healthy participants were included. The patients were assigned to 3 subgroups with functional ankle instability (FAI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…However, it has been observed that having both instabilities causes higher mental impact, more deficits in sportive activities, and lower FAAM scores. 24 In our study, CAI was not differentiated as functional or mechanical instability. Therefore, we think that future studies are needed with more sample sizes and subgroups defined.…”
Section: Discussioncontrasting
confidence: 57%
“…However, it has been observed that having both instabilities causes higher mental impact, more deficits in sportive activities, and lower FAAM scores. 24 In our study, CAI was not differentiated as functional or mechanical instability. Therefore, we think that future studies are needed with more sample sizes and subgroups defined.…”
Section: Discussioncontrasting
confidence: 57%
“…To evaluate the quality of life of people with ankle sprain injury, research has been conducted, which can be referred to the study of Haddadi et al 2020 aimed at assessing and comparing the social and psychological aspects of health-related quality of life in subgroups of people with CAI. The results showed that patients with MAI and FAI were more afraid of reinjury in daily life activities and sports activities (10). Kosik et al 2020 examined the quality of life related to local and global ankle health in participants in individuals with and without CAI and Coper, and the results showed that CAI can measure HRQOL outcomes.…”
Section: Introductionmentioning
confidence: 99%